Analysis of Parameters Variation Time Repetition; Time Echo; and Flip Angle of Signal-To-Noise Ratio and Image Characteristics 3D TOF-MRA Brain - Ariyani Eka Wardani; Sugiyanto Sugiyanto; Rasyid Rasyid (Jurnal LINK, 2012)
This type of research was an experiment, performe dat using 0.35 Tesla MRI Unit. Data obtained by performing an MRI examination of the 3 (three) patients with 9 (nine) parameter variations. Assessment is done by measuring the SNR image using software on the MRI Unit and assessment of the intensity of the arteries by making the questionnaire to 3 (three) observers to assess the degree of clarity of the anterior cerebral artery, middlecerebralartery, posterior cerebral artery, basilar artery, and vertebral artery. Then conducted an analysis of data obtained. The study states that the examinationis performed with the parameters TR 38 ms, TE 9.6 ms, and FA 30 ° has the highest SNR valuesand intensity values clarity more apparent than variations of arterie so ther parameters including routine parameters.